Augmented reality applied to language translation - Salvado, Ana Rita de Tróia (2016)
Being a tourist in a foreign country is an adventure full of memories and experiences, but it can be truly challenging when it comes to communication. Finding yourself in an unknown place, where all the road signs and guidelines have such different characters, may end up in a dead end or with some unexpected results. Then, what if we could use a smartphone to read that restaurant menu? Or even find the right department in a mall? The applications are so many and the market is ready to invest and give opportunities to creative and economic ideas. The dissertation intends to explore the field of Augmented Reality, while helping the user to enrich his view with information. Giving the ability to look around, detect the text in the surroundings and read its translation in our own dialect, is a great step to overcome language issues. Moreover, using smartphones at anyone’s reach, or wearing smartglasses that are even less intrusive, gives a chance to engage a complex matter in a daily routine. This technology requires flexible, accurate and fast Optical Character Recognition and Translation systems, in an Internet of Things scenery. Quality and precision is a must, yet to be further developed and improved. Entering in a realtime digital data environment, will support great causes and aid the progress and evolution of many intervention areas.